Unilateral Blaschkoid Linear Atrophoderma of Moulin (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Linear atrophoderma of Moulin was first described by Moulin in 1992, as an acquired hyperpigmented atrophic band along Blaschko’s lines. We present a typical unilateral Linear Atrophoderma of Moulin in a young male along Blaschko’s line. This case is presented because of its rarity and classical morphological pattern as described. Differentiation is necessary from other dermatoses, as disease progression, course of treatment, and prognosis vary according to the pathology involve.